The Art of Intelligence : Lessons from a Life in the CIA's Clandestine Service - Crumpton, Henry A. (Yew York Penguin Books, 2013)
A counterterrorism spy describes his leadership of the campaign that routed al Qaeda and the Taliban in the weeks after the September 11 attacks, offering insight into the ways in which the Afghanistan campaign changed American warfare.
Include Index
Keywords: Intelligence Officers